Solvent Additive to Achieve Highly Ordered Nanostructural Semicrystalline DPP Copolymers: Toward a High Charge Carrier Mobility. (2nd October 2013) - An, Tae Kyu; Kang, Il; Yun, Hui‐jun; Cha, Hyojung; Hwang, Jihun; Park, Seonuk; Kim, Jiye; Kim, Yu Jin; Chung, Dae Sung; Kwon, Soon‐Ki; Kim, Yun‐Hi; Park, Chan Eon
<x xml:space="preserve">Abstract</x> A facile spin‐coating method in which a small percentage of the solvent additive, 1‐chloronaphthalene (CN), is found to increase the drying time during film deposition, is reported. The field‐effect mobility of a PDPPDBTE film cast from a chloroform–CN mixed solution is 0.46 cm2 V‐1 s‐1. The addition of CN to the chloroform solution facilitates the formation of highly crystalline polymer structures. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>